Transfer of Spatial Contact Information Among Limbs and the Notion of Peripersonal Space in Insects - Dürr, Volker; Schilling, Malte (Frontiers in Computational Neuroscience, 2018)
Internal representation of far-range space in insects is well established, as it is necessary for navigation behaviour. Although it is likely that insects also have an internal representation of near-range space, the behavioural evidence for the latter is much less evident. Here, we estimate the size and shape of the spatial equivalent of a near-range representation that is constituted by somatosensory sampling events. To do so, we use a large set of experimental whole-body motion capture data on unrestrained walking, climbing and searching behaviour in stick insects of the species Carausius morosus to delineate 'action volumes' and 'contact volumes' for both antennae and all six legs. As these volumes are derived from recorded sampling events, they comprise a volume equivalent to a representation of coinciding somatosensory and motor activity. Accordingly, we define this volume as the peripersonal space of an insect. It is of immediate behavioural relevance, because it comprises all potential external object locations within the action range of the body. In a next step, we introduce the notion of an affordance space as that part of peripersonal space within which contact-induced spatial estimates lie within the action ranges of more than one limb. Because the action volumes of limbs overlap in this affordance space, spatial information from one limb can be used to control the movement of another limb. Thus, it gives rise to an affordance as known for contact-induced reaching movements and spatial coordination of footfall patterns in stick insects. Finally, we probe the computational properties of the experimentally derived affordance space for pairs of neighbouring legs. This is done by use of artificial neural networks that map the posture of one leg into a target posture of another leg with identical foot position.